2000
DOI: 10.1177/152660280000700106
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenting for Severe Radiation-Induced Extracranial Carotid Artery Occlusive Disease

Abstract: Carotid stenting is an effective treatment option for severe radiation-induced carotid artery occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 17 publications
2
19
0
3
Order By: Relevance
“…Four additional studies were retrieved from crossreferencing. [17][18][19][20] No additional studies were identified from books or abstract of major meetings. As a result, a total of 27 publications were included, comprising 533 patients divided in the CAS group (14 articles 17,19 -31 ; 361 patients, symptomatic: median 59% [Quartiles 1-3ϭ51%-75%]) and CEA group (14 articles 4,9,18,21,32-41 ; 172 patients, symptomatic: median 67% [Quartiles 1-3ϭ46%-86%]).…”
Section: Resultsmentioning
confidence: 99%
“…Four additional studies were retrieved from crossreferencing. [17][18][19][20] No additional studies were identified from books or abstract of major meetings. As a result, a total of 27 publications were included, comprising 533 patients divided in the CAS group (14 articles 17,19 -31 ; 361 patients, symptomatic: median 59% [Quartiles 1-3ϭ51%-75%]) and CEA group (14 articles 4,9,18,21,32-41 ; 172 patients, symptomatic: median 67% [Quartiles 1-3ϭ46%-86%]).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of antiplatelet, anticoagulant, antihypertensive, or lipid-lowering therapy in limiting disease progression is therefore unclear. Most studies are retrospective surgical case series on patients with extracranial carotid stenosis and favor either stenting [67][68][69][70][71] or endarterectomy. 14,[72][73][74][75] Neither approach is clearly superior, as no prospective head-to-head trial exists.…”
Section: Managementmentioning
confidence: 99%
“…В дополнение к сосудистым заболеваниям, РТ влияет на микрососудистое русло, что ведет к уменьшению коронарного резерва, ишемии мио-карда и фиброзу. Повышен риск развития сте-нозов сонных артерий и ишемического инсульта после лучевой терапии назо-фарингеальных опухолей [57][58][59][60][61][62]. Схожее по механизму пораже-ние периферических артерий от РТ отмечается у пациентов, получающих лечение по-поводу различных злокачественных опухолей брюшной полости и малого таза, хотя такие осложнения и последствия РТ встречаются реже, чем ослож-нения в виде ИБС.…”
Section: радиационная терапия и сердечно-сосудистые заболеванияunclassified